Influence of diet on nipple aspirate fluid production and estrogen levels - Morimoto, Yukiko (2011)
One possible mechanism how nutritional factors may affect breast cancer risk is through an influence on estrogen levels. Nipple aspirate fluid (NAF) is thought to provide a more direct insight into hormonal influences on breast tissue than serum. The ability to produce NAF may be an indicator of breast cancer risk. The current analysis was conducted as part of a soy trial in 92 premenopausal women and evaluated the relation of usual dietary intake with NAF volume and the most predominant steroidal estrogens in NAF and serum at baseline. Estradiol (E(2)) and estrone sulfate (E(1)S) were assessed in NAF and E(2), estrone (E(1)), and E(1)S, in serum using highly sensitive radioimmunoassays. The statistical analysis applied multivariate, log-linear regression models. Intake of saturated fat and cheese (p=0.06 for both) indicated a positive trend with NAF volume whereas isoflavonoid and soy—consumption suggested inverse associations (p=0.08 and p=0.01). For estrogens in NAF, total fat and monounsaturated fat intake was positively associated with E(2) (p=0.05 and p=0.02) and in serum, alcohol intake was associated with higher E(1)S levels (p=0.02). These findings suggest a weak influence of dietary composition on NAF production and estrogen levels in serum and NAF.